Physiological responses to overdressing and exercise-heat stress in trained runners - Ely, B.R.; Blanchard, L. A.; Steele, J. R.; Francisco, M. A.; Cheuvront, S. N.; Minson, C. T. (Medicine & Science in Sports & Exercise, 2018)
Heat acclimation is the best strategy to improve performance in a hot environment. Many athletes seeking the benefits of heat acclimation lack access to a hot environment for exercise and, thus, rely on overdressing to simulate environmental heat stress. It is currently unknown whether this approach produces the requisite thermoregulatory strain necessary for heat acclimation in trained men and women.